Safety of kidney transplantation using anti-HBc-positive donors - Abrao, J. M. G. [UNESP]; Carvalho, M. F. C. [UNESP]; Garcia, P. D. [UNESP]; Contti, M. M. [UNESP]; Andrade, L. G. M. [UNESP] (Elsevier B.V., 2014)
Background. Prospective studies evaluating the risk of hepatitis B virus (HBV) transmission in transplants of kidneys from hepatitis B core antibody (anti-HBc)-positive/ hepatitis B surface antibody (anti-HBs) negative donors are still lacking. The objective of this study was to assess the safety of kidney transplantation with the use of anti-HBc positive donors.Methods. This prospective case series study included 50 kidney transplant recipients from anti-HBc positive donors with or without anti-HBs positivity. Recipients were required to test positive for anti-HBs (titers >10 mUI/mL), regardless of anti-HBc status, and negative for hepatitis B surface antigen (HBsAg). Recipient and donor data were retrieved from medical records, databases, and organ procurement organization sheets. Liver function tests were performed at progressively increasing post-transplantation intervals. Complete serologic tests for HBV were performed before transplantation, 3 and 6 months after transplantation, and annually thereafter.Results. Six months after transplantation, all recipients were negative for HBsAg, HBeAg, anti-HBe, and anti-HBcIgM. No seroconversion was observed among the 20 patients who received kidneys from anti-HBc positive/anti-HBs negative donors. No patient showed elevated liver enzymes during follow-up.Conclusions. Kidney transplantation using organs from anti-HBeIgG positive donors (even when they are concurrently anti-HBs negative) in anti-HBs positive recipients is a safe procedure and may be considered as a way to expand the donor pool.